Pengembangan Inventori Prokrastinasi Akademik Bagi Mahasiswa - Umi Lailatussyifa’ Farida Faradila; Blasius Boli Lasan; Devi Permatasari (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
This development research aims to produce an academic procrastination scale to measure the level of delay rate to complete tasks that have high validity and reliability. So that, it can facilitate the counselors help college student with academic procrastination problems. This development study used method or strategy developed by Borg and Gall involving 300 college student. The sample of this study were 19-24 year Univercity of Kanjuruhan Malang who were selected by cluster random sampling technique, Pearson Product Moment data analysis, Cronbach Alpha, Normality test and Factor analysis. This development study produced and academic procrastination instrument consisting of 17 valid item and 5 correlated factors. So that the final result of this academic procrastination scale investment can be used for univercity counselorsnin providing follow-up service for college student.